Teachers’ Directive Speech in Character Building Values in Learning and Teaching Activities at SDN 05 Kebondalem Pemalang (Universitas Negeri Semarang, 2018)
Language serves as a means of human communication. Through communication, it will bring up speech and speech acts. Teachers have an important role in students’ character building in through speech acts during classroom teaching and learning activities. This study aimed to identify and analyze the types, functions and character values containing in the teachers’ directive speech in learning and teaching activities at SD Negeri 05 Kebondalem Pemalang. The approaches used in this study were theoretical and methodological approach. The data were in the form of teachers’ speech that contains the character values in learning and teaching activities at SD Negeri 05 Kebondalem Pemalang. The data were analyzed using SBLC technique. Based on the results of the study, the types of teachers’ directive speech at SD Negeri 05 Kebondalem were requests, questions, requirements, prohibitive, permissive and advisories. Furthermore, the speech functions found were: approving, inviting, advising, instructing, allowing, dictating, requesting, directing, granting, assigning, suggesting, demanding, interrogating, organizing, requiring, pressing, pleading, prohibiting, counseling, wanting, limiting, and forgiving. The character values found were honest, discipline, responsible, polite, care, and confident. The results of this study are expected to be useful for the development of pragmatic, especially about the study of speech act directive.